Acute flaccid paralysis surveillance data analysis, Sana’a City, Yemen, 2012-2021: A retrospective descriptive analysis - Lamya Abdo Al Aroomi; Labiba Saeed Anam; Mutahar Ahmed AL Qassimi; Faten Hamid Ezzadeen (Journal of Interventional Epidemiology and Public Health)
Background: WHO certified Yemen polio-free in 2009. Outbreaks of circulating Vaccine Derived Polioviruses (cVDPV) threaten the eventual eradication of all polioviruses. In Yemen, two outbreaks of cVDPV type 1 and 2 were reported in 2020 and 2021-2022, respectively. This study aimed to describe trends and characteristics of AFP cases in Sanaa city over the last ten years, from 2012 to 2021.